Numerical Simulation of Humidity Distribution in Solar Greenhouse. (April 2020) - Peng, Xiuyuan; Wang, Feng
Abstract: In the winter and spring when the temperature is relatively low, in order to achieve the purpose of thermal insulation, solar greenhouses usually adopt closed measures, resulting in a very high humidity inside the greenhouse. Crop growth requires a suitable environment. Too high humidity is likely to limit the progress of plant transpiration, which will lead to physiological disorders of the crop and increase the probability of crop disease. Therefore, we must grasp the law of humidity change in sunlight greenhouses, and then rationally regulate the humidity. It is of great significance. In this paper, the numerical simulation of the greenhouse environment using computational fluid dynamics (CFD) method, and the CFD numerical simulation results and experimental test results are fitted and verified, and finally the humidity distribution of the greenhouse in a certain period of time under winter irrigation conditions. In order to comprehensively understand the law of humidity change in the sunlight wet room during this period, take reasonable methods and measures to carry out artificial control to provide a suitable growth environment for crops and prevent disease from occurring. The numerical simulation results of the solar greenhouses under no-plant conditions were fitted with experimental test results. The average error between the simulated value of indoor air temperature and the actual measured value was 2.5%, and the average error between the simulated value of indoor air humidity and the actual measured value was 3.3%. The numerical simulation results and experimental test results have a higher degree of fit, which proves that the established CFD numerical model can basically reflect the internal conditions of the greenhouse.